An Examination of the Relationship Between Enclosed Residential Areas, Other Residences, and Public Spaces - Cihan, Meryem Melis; Erdonmez Dincer, Muyesser Ebru (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2018)
Globalized world order and the strengthening of neo-liberal policies since the 1970s contributed to the building of enclosed residential areas in many regions of world. The evolution of transportation and communication technologies with globalization, an increase in crime and fear that accompanied rapid population growth, and the growth of polarization between social and economic classes led many people to choose a more individual, disconnected lifestyle. As a spatial reflection of that understanding, residences are often built with strict boundaries, creating fragmentation in the city and weakening the relationship between residential areas and the city. Some existing areas are enclosed, while others are designed as restricted, gated communities. Spatial and social segregation and polarization grow. This study was an exploration of designing to fostering connections between people, rather than separation, and encouraging more social interaction through public spaces, particularly in residential areas.
Keywords: Public space; dwellings; enclosed residential areas; social segregation; spatial fragmentation; Architecture